Comparative Ratio Analysis of Financial Performance between Transportation and Logistics Sub-Sector Companies Registered on the BEI Before and During the Covid-19 Pandemic - Tresnawati, Rina; Winansih, Wiwin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to examine disparities in liquidity, leverage, profitability, and activity ratios between transportation and logistics sub-sector firms listed on the IDX before and during the COVID-19 epidemic. Employing a quantitative descriptive research design, the study encompasses companies listed from 2017 to 2019 (pre-pandemic) and from 2020 to 2022 (during the pandemic), totaling 37 companies. Through purposive sampling, 14 companies met the inclusion criteria. Data collection involved documentation techniques and utilized secondary data. The analysis was conducted through descriptive and inferential statistics, with the paired sample test applied for statistical evaluation. The findings reveal no significant differences in liquidity ratios (measured by “Current Ratio, Quick Ratio, Cash Ratio, Cash Turnover Ratio, and Inventory to Net Working Capital)” before and during the pandemic. Similarly, leverage ratios (assessed via DER, DAR, and LTDtER) and profitability ratios (measured by ROA, ROE, and NPM) showed no significant differences. However, the profitability ratio, as indicated by GPM, did exhibit a difference before and during the pandemic. There were no notable disparities in activity ratios, as assessed by WCTO, TATO, FATO, Receivable Turnover, and Inventory Turnover) across the two periods.